PLURALITAS AGAMA DI INDONESIA ANTARA INTEGRASI DAN DISITEGRASI (TOLERANSI, INTOLERANSI, POLITISASI AGAMA) - Deni Baso’; Mariati Priskilia, Agung Jaya (JOURNAL OF COMMUNITY DEDICATION, 2022)
Indonesia as a country filled with ethnicities, religions, languages, cultures, social groups and values has its own challenges. On the one hand, the diversity or plurality of religions in Indonesia is a nation's wealth that we should be grateful for, because with that wealth we can complement and enrich each other. Managing religious plurality in Indonesia is not an easy matter. On the one hand, religious people as a component of the nation try to maintain their identity and fight for their aspirations. But on the other hand, they are also required to contribute in the context of maintaining national harmony and integrity. In this regard, wisdom and maturity are needed among religious people to maintain a balance between group interests and national interests. The importance of religious openness, religion must be open and above all humanizes humans. Because how can a person claim to love an invisible God, if he refuses to love his neighbor who he can see? This open nature of religion, unfortunately, seems to be becoming increasingly rare in Indonesia along with the birth of violent religious organizations. Religious people should not find it difficult to respect the freedom of religion and belief of others. If he has faith in God, he must be able to prove that he has faith in God's sovereignty that faith is His prerogative. Thus religion will exude a humble attitude towards others, from which humanity always has hope. Violence in the name of religion does not deserve to happen, we will not assume all true beliefs. But that we don't admit it does not entitle us to impose our beliefs on others. Religion with a hard face, a religion that threatens, hates, and belittles those who are different must be rejected in this very plural nation.